Implementation of Pharmaceutical Service Standards in the Field Management of Pharmaceutical Supplies, Health Equipment and Materials Medical Consumables at Indah Ayu Farma Pharmacy Kec. Tamalanrea - Zulfiah, Zulfiah; Wahyuni, Ulva (Jurnal Farmasi Sandi Karsa, 2022)
Pharmacy is a pharmaceutical service facility where pharmacy practice is carried out by pharmacists as stipulated in the Decree of the Minister of Health of the Republic of Indonesia No. 9 of 2017. This study aims to determine the level of application of pharmaceutical service standards and the characteristics of pharmacists that affect pharmaceutical service standards in the field of pharmaceutical preparations, medical devices and medical consumables. This type of research is a cross sectional method where this study uses data collection techniques in the form of filling out questionnaires. This research was conducted at Apotek Indah Ayu Farma district. Tamalanrea. The results of this study indicate that at Apotek Indah Ayu Farma the level of application of pharmaceutical service standards in the management of pharmaceutical preparations, medical devices and medical consumables indicates that every activity carried out at Apotek Indah Ayu Farma has met or is in accordance with Permenkes No. 73 of 2016. And the characteristics of pharmacists do not affect the level of application of pharmaceutical service standards in the management of pharmaceutical preparations, medical devices and medical consumables.